Outcome of posterior versus anterior sagittal ano-rectoplasty in patients of anorectal malformation (ARM) with vestibular fistula (Journal of Paediatric Surgeons of Bangladesh, 2023)
Background: Vestibular fistula is the commonest ARM in females. Operative techniques described for treating vestibular fistula mainly include posterior sagittal anorectoplasty (PSARP) and anterior sagittal anorectoplasty (ASARP). Very few studies have been carried out to compare these two procedures. The study was aimed to compare the outcome following PSARP and ASARP for vestibular fistula.Methods: This quasi-experimental study was performed in the Department of Paediatric Surgery, Chittagong Medical College Hospital. Twenty patients with vestibular fistula, both with and without colostomy, were subjected to anorectoplasty either through PSARP (n=10) or ASARP (n=10). Patients were followed up until 3 months. Patients of both groups were compared for peri-operative and postoperative complications, cosmetic outcomes, and bowel function. Results: The two groups were comparable regarding age, maturity at birth, clinical presentation, sacral ratio, and associated congenital anomalies. Median operation time was 112.5 min for PSARP and 140.0 min for ASARP (p=0.280). Four cases had wound infection and subsequent wound dehiscence after ASARP operation and none after PSARP operation (p=0.08). Two cases had mucosal prolapse after ASARP and one after PSARP (p=1.0). All patients, irrespective of the surgical approaches, had good bowel function except one patient with ASARP who developed faecal incontinence. Conclusions: PSARP was associated with lesser complications and better cosmetic outcomes than ASARP for the treatment of vestibular fistula but these were not statistically significant.Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 13-20